1995
DOI: 10.1152/ajpgi.1995.268.3.g404
|View full text |Cite
|
Sign up to set email alerts
|

Defective interleukin-1-induced ACTH release in cholestatic rats: impaired hypothalamic PGE2 release

Abstract: A complete regulatory loop exists between the immune and neuroendocrine systems. Proinflammatory mediators such as endotoxin (lipopolysaccharide) and interleukin-1 (IL-1) are capable of activating the hypothalamic-pituitary-adrenal (HPA) axis at the hypothalamic level, presumably by inducing the synthesis of prostaglandins. We have recently identified abnormalities in the stress-induced activation of the HPA axis in cholestatic rats. Therefore, in rats with cholestasis due to bile duct resection and sham-resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
2
13
0
Order By: Relevance
“…Generally, in chronic inflammatory diseases that are associated with elevated proinflammatory cytokines (e.g., rheumatoid arthritis), hypoactivation of the HPA axis has been observed (36,98). Similar observations have also been made in experimental cholestasis (91,92,94).…”
Section: Hypothalamic-pituitary-adrenal Axis and Liver Diseasesupporting
confidence: 62%
See 1 more Smart Citation
“…Generally, in chronic inflammatory diseases that are associated with elevated proinflammatory cytokines (e.g., rheumatoid arthritis), hypoactivation of the HPA axis has been observed (36,98). Similar observations have also been made in experimental cholestasis (91,92,94).…”
Section: Hypothalamic-pituitary-adrenal Axis and Liver Diseasesupporting
confidence: 62%
“…In addition, reduced Fos expression in the hypothalamic PVN region in response to central administration of IL-1␤ has been demonstrated in cholestatic rodents, further supporting reduced neuronal activation in this region (92). Consistent with this observation, the increase in ACTH release typically observed in response to central IL-1␤ administration was markedly reduced in cholestatic rodents (94). CRH has been shown to have behavioral activating effects.…”
Section: Hypothalamic-pituitary-adrenal Axis and Liver Diseasesupporting
confidence: 55%
“…Resection of the bile duct in rats leads to impaired stress-induced CRH release compared with controls, which results in decreased circulating ACTH levels (46,48). ACTH release from the pituitary as a result of IL-1␤ treatment is also dampened after bile duct resection (47). Furthermore, McNeilly et al (37) recently suggested that bile acid buildup as a result of cholestasis may have the ability to inhibit hepatic glucocorticoid clearance, thereby allowing glucocorticoid levels to increase to a level that would inhibit the HPA axis.…”
Section: Discussionmentioning
confidence: 99%
“…However, patients with RA fail to increase cortisol secretion following surgery, despite high circulating IL-1β levels, suggesting that a defect exists in the hypothalamic response to IL-1β in these patients [57]. In addition, rats with experimental cholestatic liver disease exhibit defective stimulation of ACTH release after the peripheral administration of IL-1β, consistent with abnormal hypothalamic CRH responsiveness to this cytokine in these animals [58].…”
Section: Cytokines and Immune Activationmentioning
confidence: 97%